Study on the association SLC2A9 RS12510549 with uric acid and gout in Vietnamese population - Minh Thang, Nguyen Tran; Doan Tinh, Nguyen; Van Hai, Nong; Thuy Duong, Nguyen (Vietnam Journal of Biotechnology, 2020)
Gout is the most common form of arthritis in Vietnam and around the world, caused by an excess of blood uric acid levels. The occurrence of gout is influenced by many risk factors such as diet, living and genetic factors. Studies showed gout is associated with polymorphisms located on genes that encode transport protein channels, including SLC2A9 rs12510549. To evaluate the association of polymorphism SLC2A9 rs12510549 to uric acid levels and gout in the Vietnamese population, we genotyped rs12510549 of 519 subjects (168 gout patients and 351 healthy people) by the PCR–RFLP method. The relationship between genotype distribution, the allele frequency of polymorphism with uric acid levels and gout was assessed through statistical methods. The results show that SLC2A9rs12510549 was in accordance with HWE (p> 0.05) and the genotype frequencies of TT, TC and CC were 0.73, 0.25 and 0.02, respectively, confirming the randomness and representation of the study population. The genotype distribution and frequency of the rs12510549 allele were determined unrelated to uric acid levels and gout in the Vietnamese population (p>0.05). Further study with a larger sample size should be implemented to confirm our results on the association of SLC2A9rs12510549 and gout in the Vietnamese population.